Large Assemblage of Seventeenth- and Eighteenth-Century British and Spanish Glass from Buenos Aires, Argentina - Schavelzon Chavin, Daniel Gaston (2015)
Two archaeological excavations made in Buenos Aires, Argentina, between 2007 and 2013, have made it possible for the first time to recover significant groups of European glass fragments (English, Spanish, Dutch and Italian) dating to the seventeenth and early eighteenth centuries. The two groups of glass objects were found at two archaeological excavations corresponding to two separate dwellings located just over a hundred feet apart within the same block, at 375 Bolivar Street and 460 Venezuela Street under the direction of the author and Flavia Zorzi, in an area in the centre of the city where excavations have been going on for over twenty years, and where only isolated fragments of glass from those dates had been recorded.